Spoczynkowe stezenia kortyzolu i testosteronu we krwi u kolarzy w okresie treningowym i startowym - Obminski, Z.; Szuczypaczewska, M.; Tomaszewski, W. (Medycyna sportowa, 2001)
Cortisol (C) and testosterone (T) concentrations, as well as the so-called anabolic-catabolic index (T/C'102) were determined in venous blood plasma of 25 cyclists. Blood was sampled in the morning, at rest, at the end of the training season (February) and in the competition season (July). Mean (± SD) cortisol level in the training season tended to lower than in the competition period (437 ± 131 vs. 486 ± 143 nmol/L; p < 0,10). On the other hand, mean testosterone level and the T/C ratio were significantly higher in the training season compared with the competition period (18,6 ± 5,5 vs. 15,9 ± 3,6 nmol/L, and 4,6 ± 2,2 vs. 3,6 ± 1,5, respectively; p < 0,05). The decrease of testosterone concentrations in the competition period, observed in endurance cyclists, as well as changes in the hormonal balance, enhance catabolic processes in that period.